The Relationship between Religiosity and Peer Social Support with Student Courtesy Behavior - Azzahro', Adibatul Bahiroh; Wahyuni, Esa Nur; Sudirman, Sudirman (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study addresses growing concerns over declining moral standards among university students in the context of globalization and rapid technological advancement, with a particular focus on examining the influence of religiosity and peer social support on polite behavior among students at UIN Malang. Utilizing a correlational quantitative research design, data were collected from 271 respondents selected through the Cochran sampling technique. Structured questionnaires served as the primary data collection instrument, and the responses were analyzed using multiple linear regression. The findings indicate a statistically significant joint influence of religiosity and peer social support on polite behavior, as evidenced by an F-test significance value of 0.000 < 0.05, and a combined explanatory power of 54.4%. Notably, peer social support exerted a stronger effect (β = 1.050) on students’ courteous behavior compared to religiosity (β = 0.155), highlighting the prominent role of social interactions in shaping moral conduct. These results underscore the importance of fostering a supportive peer environment as a key strategy for promoting ethical behavior among university students, alongside ongoing efforts to reinforce religious values. The study contributes to the understanding of behavioral development in higher education and suggests actionable insights for student affairs practitioners and educators aiming to enhance moral character in academic settings.